Development and Assessment of Mucoadhesive Buccal Tablets Containing Dapsone: A Pharmaceutical Innovation - Parameshwar, Kondapuram; Gunda, Raghavendra Kumar; Rasheed, Shaik Harun; Muralidharan, Venugopal; Shankar, K Ravi (Indian Journal of Pharmaceutical Education and Research, 2026)
Objectives: This research involved developing buccal tablets with the drug Dapsone, using varying amounts of three substances: Carbopol 934, Hydroxypropyl Methylcellulose, and Sodium Carboxymethyl Cellulose. Materials and Methods: Twelve different tablet formulations were produced using the direct compression technique. These tablets were tested for various physical and chemical attributes, such as hardness, size, weight consistency, drug concentration, tendency to crumble, absorbency, surface acidity, and adhesive strength. The dissolution of the tablets was tested over 12 hr using a method from the Indian Pharmacopeia 2018, involving a rotating paddle in a pH 6.8 buffer. Results: The study found that the tablets met Pharmacopeia’s standards in terms of weight, hardness, friability, diameter, thickness, and drug concentration. The swelling index varied from 112.93% to 455.12%, and the surface pH was stable between 6.72 and 6.96. Adhesive strength differed based on the concentration of carbopol 934. There was a wide range in the drug release rates among the different batches, with the highest being 99.66% and the lowest 45.22%. Only one batch achieved an effective and sustained release of 88.4%, with an ideal swelling index and adhesive strength. Fourier Transform Infrared Spectroscopy showed no interaction between the drug and the other tablet ingredients. Conclusion: The study concluded that it's possible to create effective Dapsone buccal tablets, and their characteristics are largely determined by the polymers used.
Keywords: Dapsone; Swelling index Mucoadhesion; Buccal tablets